Use of body linear measurements to estimate the reproductive performance of cattle in smallholder farms by a participative breeding system in South Sulawesi, Indonesia. Issue 1 (June 2021) - Zulkharnaim,; Baco, S; Ako, A; Baba, S; Rahim, L; Syarif, I; Hasman,
Abstract: Study aimed to identify the correlation of body sizes of Bali cattle with the pregnancy ability trait. Many studies gave attention to the body characters of beef cattle as the object being observed. Several types of research reported a strong correlation between some linear body sizes with some production traits. The pregnancy trait in beef cattle is very important, especially for smallholder farmers. A total of 100 cattle were measured body sizes, includes 50 pregnancy cattle and 50 non-pregnancy cattle. Three morphometric traits were measured on each animal. The parts measured were body length (BL), withers height (WH), heart girth (HG) and body condition scoring (BCS). The morphological traits were analysed using descriptive statistics using IBM SPSS Statistic 20 and Microsoft Excel. Relationship between HG and BCS on pregnant cow followed a regression equation Y= 0.0721X - 4.447 (R 2 = 68, 3%) and on an-pregnant cow followed Y= 0.0953X - 7.3978 (R 2 = 68, 3%). The relationship between heart girth and body condition scoring is very close and can be used to predict pregnancy ability in cows. The regression equation will greatly help smallholder farmers in the participatory breeding system.